2019
DOI: 10.23887/leju.v2i1.20276
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Grammatical Errors Made by the Seventh Grade Students of SMP Negeri 2 Sukawati in Writing Descriptive Texts in the Academic Year 2018/2019

Abstract: This study aimed at describing the types of errors in seventh grade students’ descriptive texts and identifying causes of errors. There are two research questions in this study, namely: (1) What are types of grammatical errors made by seventh grade students of SMP Negeri 2 Sukawati in writing descriptive texts? and (2) What are the causes of grammatical errors made by seventh grade students of SMP Negeri 2 Sukawati in writing descriptive text?. The data for study were collected by document study, interview met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…In this sentence, the student removes the marker or apostrophe's (possessive form) in the word father so that the sentence is not grammatically correct. In this case, the forms of errors seen by Erlangga, Suarnajaya, & Juniarta (2019) can also occur in other students. Therefore, this analysis is important to make effective English teaching, which is focused on fostering students' narrative writing skills.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this sentence, the student removes the marker or apostrophe's (possessive form) in the word father so that the sentence is not grammatically correct. In this case, the forms of errors seen by Erlangga, Suarnajaya, & Juniarta (2019) can also occur in other students. Therefore, this analysis is important to make effective English teaching, which is focused on fostering students' narrative writing skills.…”
Section: Introductionmentioning
confidence: 91%
“…In the same vein, Tarigan (1987: 12) also revealed that the quality of students' language learning outcomes is still not satisfactory. One of these can be seen in the analysis of errors in student writing conducted by Erlangga, Suarnajaya & Juniarta (2019), which found forms of errors such as omissions such as my father* name is Sukaarta where the correct form is my father's name is Sukaarta. In this sentence, the student removes the marker or apostrophe's (possessive form) in the word father so that the sentence is not grammatically correct.…”
Section: Introductionmentioning
confidence: 99%
“…Carelessness is related to the low motivation of students (Norrish, 1983). In this case students do not have enough motivation to know more about something since the material is not interesting or the students do not feel comfortable with their teacher's teaching styles (Erlangga et al, 2019).…”
Section: Misformation Errormentioning
confidence: 99%
“…Furthermore, Erlangga et al (2019) conducted an analysis of grammatical errors prevalent in descriptive texts authored by seventh-grade students. Their work identified common grammatical pitfalls, providing valuable insights for educators aiming to address these issues effectively in the classroom.…”
Section: Introductionmentioning
confidence: 99%